[Mari Katus 2]
slicing cake, in the cemetary, wiew from the Gellert-mountain, newborn baby, castle of Vajdahunyad, family together at grandma, baby in different positions, with grandparents, 1973 Zolika 2 years old, birthday cake, Öcsike 1year old, swinging